Climatic Changes and Global Fisheries: The Nigerian Experience - Ekpo, Ekpo Imoh (Richtmann Publishing, 2012)
Climatic change is a significant and lasting change in the statistical distribution of weather patterns overperiods ranging from decades to millions of years. Millions of people around the world depend on fish forincome and livelihood. Linked to the strong increase in fish production, employment in capture fisheriesand aquaculture has grown substantially in the last three decades, with an average rate of 3.6 percent.Climatic changes affects spawning sites of fisheries resulting in the reduction of fish biomass, destruction ofcoral reeves, distortion of food web and food chain, and the reduction of caught fisheries. Shifts in oceansalinity are occurring, with near-surface waters in the more evaporative regions of most of the world’socean increasing in salinity, while marine areas in high latitudes are showing decreasing salinity due togreater precipitation, higher runoff, melting ice and other atmospheric processes. Importantly, increase insalinity affects fish spawning site which in turn influences fish population. This will translate to less incomefor fishers as they record less catch. In an attempt to meet up other social responsibilities, fishers mayresort to other more dangerous methods of catching fish like toxic chemicals, explosives and dynamite.Serious sanctions must be put in place to restrain fishers from adopting these dangerous methods ofcatching fishes while effort must also be intensified to improve aqua culture production